Inflammation and Vascular Injury - Rizzo, Toni (MD Conference Express, 2012)
The focus this article is on a class of leukocyte adhesion molecules, leukocyte β2-integrins, among which Mac-1 (aMb2, CD11b/CD18) is the most common integrin on neutrophils. The leukocyte Mac-1 receptor interacts with the glyocoprotein Iba (GPIba) receptor on platelets, thereby regulating pro-inflammatory and pro-thrombotic bidirectional signals in both inflammatory cells and platelets.